OCCURRENCE AND IDENTIFICATION OF Bacillus SPECIES FROM DIFFERENT SOURCES OF HONEY (FUDMA JOURNAL OF SCIENCES, 2020)
Honey is a sweet viscous liquid produced by honey bee Apis mellifera from the nectar of plants. This study was carried out to determine the occurrence and identification of Bacillus species in honey samples from apiaries, locally harvested, commercial and packaged honey samples marketed in some states of Nigeria. Twenty seven honey samples were obtained from: Abia, Enugu, and Benue and Rivers state.  Honey samples were diluted with sterile distilled water and pour plated onto Hi-Chrome Bacillus agar. The isolates were identified using chromogenic media, phenotypic and Analytical Profile Index (API) kits (AP 50CHB). Nine species of Bacillus species identified include: Bacillus badius, B. cereus, B. circulans, B. laterosporus, B. licheniformis, B. megaterium, B. mycoides, B. polymyx and B. subtilis. The Bacilli count for honey samples were in the range 3.48 -2.96 log cfu/ml (Abia), 3.44 - 3.20 log cfu/ml (Benue), 3.36 - 3.15 log cfu/ml (Enugu) and 2.91-3.40 log cfu/ml (Rivers state) respectively. The occurrences of Bacillus species were significantly higher (p0.05) between the branded product samples and those from apiaries. This study has demonstrated that Bacillus species are prevalent in different sources of honey
Keywords: Apiaries, Honey, Prevalence, Bacillus, Hi-Chrome Media, Characterization